Producing Inclusive Space: The Kotabaru Jazz Festival and Interreligious Spatial Practices in Indonesia - Abdillah, Arafat Noor; Hamsah, Ustadi (Religió Jurnal Studi Agama-agama, 2025)
This article analyzes the Kotabaru Jazz Festival in Yogyakarta as a form of inclusive spatial production within the context of Muslim-Christian relationships. Using a descriptive qualitative approach and Edward Soja’s Thirdspace framework, this article explores how public space in the Kotabaru cultural heritage area has been reproduced through collaborative work across religions, communities, and social institutions. Data were obtained through participant observation, semi-structured interviews, and field documentation. The research findings indicate that the festival is not merely a cultural event, but also a spatial practice that combines three spatial dimensions: physical space, representational space, and lived space. The use of spatial elements such as churches, mosques, heritage buildings, and public streets serves as a symbol of diversity and nationalism. Interactions between individuals and groups during the festival create tangible forms of interfaith solidarity. The visual representations, artistic expressions, and public narratives present in the festival form a symbolic space that encourages social inclusion and opens up space for interfaith pedagogy. This article confirms that festivals as social and cultural practices have the potential to create dialogical spaces and strengthen social cohesion in multifaith societies in a postcolonial context.